2014
DOI: 10.3844/ijrnsp.2014.17.26
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Overseas Nurses Caring for Muslim Patients in Kingdom of Saudi Arabia and Uae: A Qualitative Study

Abstract: Cultural competence in nursing care has always been emphasized and recommended as a quality indicator and a core knowledge requirement for all nurses. However, the provision of such culturally competent care can only be achieved when patients' cultural values and systems are known to the nurses and used appropriately to inform their practices. This study will help to reveal the different components of nurses' experiences while caring for patients from Islamic culture. This will inform the practice of service p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…"But there are also acculturated Westernoriented Muslims -or 'cultural Muslims' -who may or may not adhere strictly to the practices of Islam" [23] (p.12). This is also supported by a study conducted by AIYateem et al [15] who found that religion was a constant practice, exponentially more so when patients were ill or dying "more so than surgery or nursing procedures" (p. 23). However, findings indicated that HCPs who moved to the Middle East who did not have this concept embedded into their practice, lead to misunderstandings between the patient and the nurse.…”
Section: Cultural Knowledgesupporting
confidence: 57%
See 1 more Smart Citation
“…"But there are also acculturated Westernoriented Muslims -or 'cultural Muslims' -who may or may not adhere strictly to the practices of Islam" [23] (p.12). This is also supported by a study conducted by AIYateem et al [15] who found that religion was a constant practice, exponentially more so when patients were ill or dying "more so than surgery or nursing procedures" (p. 23). However, findings indicated that HCPs who moved to the Middle East who did not have this concept embedded into their practice, lead to misunderstandings between the patient and the nurse.…”
Section: Cultural Knowledgesupporting
confidence: 57%
“…However, once embedded in a culture unlike our own, it is difficult to imagine that things we see are not abnormal for those that live within that culture. [14] According to AI Yateem and AI-Yateem [15] HCPs need to be aware of the different cultural meanings patients and nursing students ascribe to certain behaviors; yet this has not always been well received. Being culturally aware is the epitome of becoming culturally competent, which helps to recognize discrimination and avoid stereotyping.…”
Section: Cultural Awarenessmentioning
confidence: 99%
“…Religion and culture play an important role in shaping the values and beliefs of people in Saudi Arabia (Abudari et al, 2016; AlYateem & Al‐Yateem, 2014). During sickness and suffering, cultural practices remain embedded in daily lives even when people are hospitalized as reflected in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional health practices mandate spiritual healings that involve reading scriptures from the Quran, and the use of Zamzam water, a holy water from the Zamzam well in Makkah, and honey, and black cumin (Al‐Shahri, 2002). Drinking Zamzam water and reading verses from the Quran, and prophetic supplications are often practiced before placing liquids and/or oils on the patient (Abudari et al, 2016; AlYateem & Al‐Yateem, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A similar quantitative study on the cultural adaptability Registered nurses in the GCC identi ed that language, work ethics, religious practices and climatic differences were signi cant adjustments that the Filipino nurses in the GCC need to be adapted to. (Valdez, 2016) (Al-Yateem & Al -Yateem, 2014). The study endeavors to explore the cultural lived experiences of the IRN's in Oman.…”
Section: Introductionmentioning
confidence: 99%